Production of Biodiesel from Waste Cooking Oil and Its Performance on Four Strokes IC Engine - S V S R Krishna, B.; B K, Shivaraj (International Journal of Engineering and Technology, 2018)
Majority of biodiesel is produced from plant oil (Jatropha, Pongamia, Mahua, Neem, Cotton seed oil etc.), which requires large land area to grow. The major drawback of production of biodiesel in large scale is the cost of raw materials. One of the satisfactory methods to limit the Biodiesel (Methyl esters) production cost is to employ low price/quality raw material, for instance biodiesel production using waste cooking oil (WCO). Simultaneously solves the disposal problem of waste cooking oil. This is socioeconomic and environment friendly and it does not compete with fresh food oil resources. Waste cooking oil collected from different hotels in and around Manipal/Udupi of Karnataka, India. Transesterification reaction of WCO with methanol in presence of alkaline catalyst KOH has been accomplished in transesterification reactor. Experiments have been carried out at different operating conditions viz. catalyst loading (over the range of 0.4 to 3 wt %), oil to methanol ratio (1:3, 1:5, 1:6, 1:8, 1:9, 1:10 and 1:12), reaction temperature (50, 60 and 70 ºC) and reaction time (40, 50, 60, 70, 80 and 90 minutes) to identify optimized conditions for preparation of biodiesel. At these conditions gave that maximum yield ( 91.60 %) of biodiesel at catalyst loading of 0.85 wt %, oil to methanol ratio of 1:8, reaction temperature of 60 ºC and reaction time of 60 minutes. Biodiesel properties at different blends (B100, B30, B20, and B5) as prescribed by ASTM D6751-12 methods have been carried out. Its performance and emission test on diesel engine were also carried out.